Strategic management in new ventures: the role of technological, organizational and environmental factors - Shahidifar, Ehsan (Journal of Entrepreneurship, Business and Economics; Vol 4 No 2 (2016), 2016)
Today, as firms become more competitive in their fields, the use of strategic insights and management practices are becoming an integral part of the firms' activities- especially for new ventures which are in the early phases of their lifecycle. Indeed, they cannot improve their performance if they do not take advantage of such tools and mechanisms. On the other hand, nascent firms are facing lots of problems due to the lack of appropriate use of strategic insights. One of the main problems is the acceptance of strategic management practices in such companies. Then, in this paper, the authors try to investigate the elements which affect their acceptance. Authors use technology-organization-environment (TOE) framework to examine the hypotheses. Findings reveal that all the factors were influential, other than complexity, vendors' support, firm size, and industry type. Research paper Reference to this paper should be made as follows: Shahidifar, E. (2016). ―Strategic management in new ventures: the role of technological, organizational and environmental factors‖, Journal of Entre-preneurship, Business and Economics, Vol. 4, No. 2, pp. 130–149.